MEMBENTUK FAKULTAS PSIKOLOGI ISLAM PROFESIONAL - Ismail, Rahmat (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2004)
In this globalization era, the boundaries of region or country are not so clear, as the result, collisions and competitions in any aspect cannot be avoid. Psychology faculty of UIN Malang also should have been ready to face that condition, because who is lost will be thrown away. Therefore to prepare for that psychology faculty, at least, should realize these five points: 1. Transform the classic paradigm to the new paradigm, 2. Develop the strong foundation for high morality, 3. Expert in foreign language, 4. Have good skill in technology (computer), 5. Have good leadership.For the first point, it is not only transforming the classic paradigm to the modern paradigm, but also transforming paradigm that Islam is only ritual religion to paradigm that Islam is both ritual and social religion. As the result, Islamic subject in psychology faculty is not to function only as complement, but as inspiration for all subjects. Furthermore, it is expected that the output of psychology faculty will become a professional, which has a good vision and high morality.Keywords: Psychology faculty, professional, and Islam.Â Â